Pattern-Sensitive Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical and electroencephalographic (EEG) findings of 73 (43 female and 30 male) patients diagnosed with pattern-sensitive epilepsy between 1950 and 1999 were evaluated at the Mayo Clinic, Rochester, MN.